Exploring students’ achievements in differential equations courses and their feelings towards mathematics courses - Nur Arzilah Ismail,; Nuryazmin Ahmat Zainuri,; Noorhelyna Razali,; Zulkifli Mohd Nopiah,; Muhamad Alias Md. Jedi,; Haliza Othman,; Wan Zawiah Wan Zin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Differential equations are a fundamental area of mathematics that is widely used in various fields, including physics, engineering, economics, and more. However, many students find this course to be particularly challenging and struggle to achieve success in differential equations courses. Therefore, this study aims to investigate the relationship between students’ achievements in midterm and final exams differential equations courses and their feelings towards mathematics courses, to provide a more comprehensive understanding of the factors that contribute to success in this challenging course. The results of this study indicate a positive correlation between students’ achievements in differential equations courses and their feelings toward mathematics. Male students performed slightly better than female students for marks above 50. Additionally, students who enjoyed all the mathematics courses had higher grades in differential equations courses, which was statistically significant. These findings also highlight the importance of midterm exams as preparation before seating for the final exam of differential equations.